Design of A New Three Phase Hybrid H-bridge and H-Type FCMLI for Various PWM Strategies - Chinnapettai Ramalingam Balamurugan; S.P. Natarajan; V. Padmathilagam; T.S. Anandhi (Institute of Advanced Engineering and Science, 2015)
The inverters have to be designed to obtain a quality output voltage or a current waveform with a minimum amount of ripple content. In high power and high voltage applications the conventional two level inverters, however, have some limitations in operating at high frequency mainly due to switching losses and constraints of the power device ratings. Series and parallel combination of power switches in order to achieve the power handling voltages and currents. The conventional two level inverters produce THD levels around 60% even under normal operating conditions which are undesirable and cause more losses and other power quality problems too on the AC drives and utilities. Nowadays, multilevel inverters are widely used in power industry. Voltage unbalance problem is one of the major issues in working of multilevel inverter. In this paper, a three phase H-bridge + H-type FCMLI using sinusoidal reference, third harmonic injection reference, 60 degree reference and stepped wave reference are initially developed using SIMULINK and then implemented in real time environment using dSPACE. The five level output voltages of the chosen MLIs obtained using the MATLAB and dSPACE based PWM strategies and the corresponding % THD, VRMS (fundamental) , CF and FF are presented and analyzed. It is observed that bipolar COPWM-C provides output with relatively low distortion for sine reference and bipolar COPWM-B strategy is found to perform better since it provides relatively higher fundamental RMS output voltage for 60 degree reference.